Adaptive Classroom Management Strategies and Student Learning Discipline in a Rural Elementary School - Riska Tolodo; Bau Ratu; Pahriadi Pahriadi; Herlina Herlina; Muhammad Fasli (Journal of Innovation and Research in Primary Education, 2026)
Effective classroom management is fundamental to fostering student learning discipline, yet empirical evidence from rural, resource-constrained elementary schools remains limited. This study examined how teachers' classroom management strategies contribute to creating a conducive learning environment and improving student discipline in such an underrepresented context.  A qualitative descriptive design was employed at SDN Inpres Sumondung, Banggai Islands Regency, Central Sulawesi. One Grade III classroom teacher and four students were selected through purposive sampling. Data were collected via structured classroom observations, semi-structured interviews, and documentation, then analyzed using Miles et al.'s (2014) interactive model,  comprising data reduction, display, and conclusion drawing ,  with triangulation to ensure trustworthiness.  Five classroom management strategies were consistently observed: collaborative rule-setting, flexible physical environment arrangement, structured instructional time management, persuasive teacher–student interaction, and systematic positive reinforcement. Student learning discipline was predominantly demonstrated through punctual attendance and assignment completion, while rule compliance during learning remained partial.  These strategies collectively fostered a participatory and relational classroom climate that supported student discipline even under severe infrastructural constraints. Notably, teacher-improvised micro-zone arrangements produced unexpected reductions in off-task behavior, suggesting that spatial agency can partially compensate for resource deficits.  Adaptive, relational, and participatory classroom management practices can effectively cultivate learning discipline in rural elementary schools, advancing the proposition that teacher agency, not resource adequacy, constitutes the primary determinant of management effectiveness.